Conceptualizing meaningful tourism experiences: Case study of a small craft beer brewery in Thailand - Rangson Chirakranont (2022)
An experience-driven conceptualization to understanding craft beer tourism is explored through the case study of a small brewery in Thailand. Adopting a four-pronged qualitative research design, the study reveals how the combined values of staged experiences, co-creative experiences and transformative experiences, and certain pre-conditions (i.e. traits of the tourism provider and categories and motivations of the tourists) that foster those experiences can lead to meaningful tourism experience of a single tourism destination. The study contributes to social exchange theory and positive psychology in tourism, while offering practical guidelines for tourism stakeholders involved in the development and promotion of tourism experiences.